Ações para a melhoria da satisfação do trabalhador em canteiros de obras - Priori Junior, Luiz (2007)
This dissertation has as its object of study quality of life and safety at work on building sites and aims to analyze the commitment of civil construction companies who have a system of quality management set up and certificated in accordance with NBR ISO 9001:2000 with safety and quality of life in the work of their employees on building-sites. Specifically, an investigation is made, based on the Policy and Quality Objectives adopted by construction companies who engage in the sector of vertical buildings, in the Metropolitan Region of Recife, whatever may be the determining data for this enterprise and the types of objectives which include each of the sectors researched, namely Safety at Work and Quality of Life at Work. The methodology used, based on case studies, initially considered the analysis of the recognizably successful experience of one civil construction company which implemented actions for improving quality of life on its building sites. Thereafter, using the data collected in selected companies, pieces of information were obtained which pointed to features lacking in the objectives of the system of quality management which contemplated the object of this study. Therefore, as a practical suggestion arising from this study, ten actions have been proposed for improving the conditions of life and/or safety of workers on building-sites, set out step-by-step, in such a way as to guide and facilitate their implementation by building firms.